Current status of transcriptome sequencing technology in ruminants - JiaYu, Cui; Lili, Song; Dawei, Wang; ZhiLin, Liu; Xin, Zhang; Zelin, Jia; Yuhang, Zhang; Huisheng, Xiong; Xueli, Wang (Frontiers in Veterinary Science, 2025)
In many parts of the world, safe ruminant production underpins food security, while ruminant meat and milk are important agricultural commodities and a major source of protein requirements in the human diet. In order to maintain the sustainability of such agricultural products, animal production should be made more efficient through better management and production techniques. Ruminating animals such as cows and sheep have been used for the synthesis of dairy products, the production of high-quality meat, and the study of reproductive mechanisms. Using transcriptome technology in ruminant ecosystems has sped up the study of animal diversity under various feeding and production conditions. These studies have provided sufficient information to reduce farm pollution and improve farming efficiency. Transcriptome sequencing can be used to explore specific indicators at a deeper level, such as the content (high and low) and composition of intramuscular fat (IMF) in meat processing, the expression of DEG-related hormones, the regulation of bile acid concentration on fat precipitation, and the regulation of growth and meat quality properties in cattle and sheep. During the lactation stage of ruminants, transcriptome sequencing is used to screen for differentially expressed genes in blood tissue, which can identify candidate functional genes for milk production traits. Transcriptome sequencing can detect genes with low expression levels, identify new gene transcripts and alternative splicing events, detect and analyze the biological regulatory mechanisms of the body, reveal differences in gene expression levels during breeding, and reveal the interaction between hosts and pathogens. This sequencing technology can also help understand the immunobiological situation during infection. This paper reviews the current status of transcriptome sequencing and the application of transcriptome sequencing technology in ruminants, with a view to providing theoretical reference and basis for the better application of transcriptome sequencing technology in ruminant research.